Improving Early Childhood Linguistic Intelligence Through Picture Card Media at RA Al-Ihya - Atikah Sri Wahyuni; Fifi Ratnawati; Nunung Nuraini; Raina Dininda; Siti Rohmawati; Yayan Sudrajat (Journal of Instructional Development, Innovation, and Evaluation, 2023)
This research discusses Improving linguistic intelligence of early childhood by applying picture card media at RA Al-Ihya, Depok. This research is a type of classroom action research that refers to the Kemmis and MC models. Taggart includes four stages, namely (1) planning (2) action (3) observation and (4) reflection. This research consists of 2 cycles, each. The cycle consists of 4 meetings. The data analysis technique used in this research is qualitative and quantitative data analysis. The sample of this study were 15 students of RA Al-Ihya, Depok. The aims of this study were (1) to improve the linguistic intelligence of children aged 5-6 years at RA AL-Ihva, Depok. (2) The results of increasing the linguistic intelligence of children aged 5-6 at RA Al-Ihya, Depok. Data collection techniques in this study used observation sheet instruments, interviews, and documentation.   The results of this study stated that there was an increase in children's linguistic intelligence, namely 46% in cycle 1 and in cycle II to 54%. The research findings show that applying pictorial kart media can improve early childhood linguistic intelligence